PENGARUH STRUKTUR KEPEMILIKAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEPUTUSAN PENDANAAN DAN NILAI PERUSAHAAN - I Gede Surya Pratama; Ida Ayu Agung Idawati; Ade Ruly Sumartini (UNHI Press, 2018)
The aim of the company is to maximize the value of the company through the implementation of financial decisions consisting of investment decisions, funding and dividend policies. Companies tend to use debt in order to increase the value of their company. If a manager is able to increase the value of the company, the manager has shown good performance for the company. To increase corporate value, a good funding and investment decision is needed. The purpose of this study was to determine the effect of institutional ownership and company growth on funding decisions and the value of manufacturing companies. The population of this study was 152 and was selected by purposive sampling so that 129 samples were obtained. Data Analysis Techniques use Path Analysis. Hypothesis test results show that the level of debt held by the company is influenced by institutional ownership and growth of the company. While the high and low values ​​of the company are influenced by institutional ownership, the level of corporate debt and company growth.